3500 years of environmental sustainability in the large-scale alpine mining district of Hallstatt, Austria. (February 2021) - Festi, Daniela; Brandner, Daniel; Grabner, Michael; Knierzinger, Wolfgang; Reschreiter, Hans; Kowarik, Kerstin
Highlights: Study indicates salt extraction in Hallstatt already in the 4th mil BCE. Prehistoric mining impacted on tree cover to the same extent as industrial mining. Prehistoric miners were perceptive of limits and hazards of this landscape. Model of low impact of early mining systems on tree cover needs to be revisited. Human presence from Bronze Age to present and high level of resilience. Abstract: Throughout time, salt has played a crucial role in societies representing one of the most precious natural raw materials that can be extracted from the environment. The Austrian Alps are home to the world's oldest and extensively studied record of large-scale underground salt mining: the UNESCO World Heritage site Hallstatt-Dachstein/Salzkammergut. In this study, we focus for the first time on the impact that the salt extraction had on the vegetation and the environment throughout the millennia, presenting the first paleoecological data for the mining area, which have been obtained from a peat bog located near the mines. Our study indicates that salt extraction started already in the 4th mil BCE, and phases with the highest impact on the vegetation are documented in the Bronze Age (around 1350 BCE) and the Modern Era (15th-19th century CE). Our record also reveals an environmental awareness of the miners, as natural resources of the region were never depleted in order to provide material needed for the mines (construction materials, subsistence goods, etc.).